Impact of children’s appropriate work participation in cocoa farms on household welfare: Evidence from Ghana - Enoch Kwame Tham-Agyekum; Camillus Abawiera Wongnaa; Nana Afranaa Kwapong; David Boansi; Fred Ankuyi; Stephen Prah; John-Eudes Andivi Bakang; Ernest Laryea Okorley; Ezekiel Laten (Journal of Agriculture and Food Research, 2023)
This study examines how children engaged in cocoa farming in Ghana affect household welfare. Data was gathered from 384 cocoa producers using a multistage sampling technique and analysed employing the Cragg double hurdle and propensity score method. The study found that only 2.3 % of cocoa farmers highly used children for cocoa activities. Additionally, household size, cooperative membership, and credit access were found to have significant impacts on both the use and extent of use of children on cocoa farms. Moreover, cocoa farmers who used children experienced improvements in their income, food security and assets compared to those who did not use children. The study also confirms the reality of the practice of employing children on cocoa plantations in Ghana. Harnessing the considerable advantages of credit access and cooperative membership, we emphasize the importance of extension agents sensitizing cocoa farmers about the merits of forming cooperatives. This approach could serve as a means of obtaining group/individual credits to support cocoa production. Furthermore, in light of the notable improvements in the welfare of cocoa farmers, it is imperative for COCOBOD to take decisive action in invigorating the regulation against child labor and instead embrace agricultural technologies as viable alternatives.